Block chain-Based Solutions for Improved Cloud Data Integrity and Security - Md Tanvir Rahman Tarafder; Arafath Bin Mohiuddin; Nisher Ahmed; Md Abu Shihab; Md Farhad Kabir (BULLET : Jurnal Multidisiplin Ilmu, 2022)
The evolution of cloud computing, however, has not been all smooth sailing, and it still struggles with data security and trusted computing to this day. Alternative solutions like data integrity tests and secure multi-party computation is often accompanied by computational complexity and scalability concerns. Block chain technology has been developed as an abstract setting of decentralized distributed computing, and applied to secure storage and computation in various cloud environments. In response, we propose a distributed virtual machine agent model that uses the mobile agent technology to create a cooperative and multi-tenant environment for the verification of trust in the data. This model assures the data are stored and monitored reliable way and provides a verification method that is the base of a Block chain based integrity protection mechanism. Using this model, we create a Block chain model that utilizes Merkle hash trees in order to create unique file hashes. Smart contracts monitor changes to this data and will notify users of any tampering. Additionally, in a block-and-response manner, it provides a strong cloud data integrity verification solution.